Survey Keterampilan Teknik Dasar Tenis Lapangan Pada Atlet Tenis Kota Medan - Nurkhadri Nurkhadri; Gres Nina Natalia Br Sembiring; Apul Danikesuma Ginting; Chrismanto Panjaitan; Martinus Vincent Debataraja; Everanza Perdana Ginting (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
This study aims to determine the extent basic tennis technic skill. The method in this study uses a survey method with data collection technique using tests and measurements. The instrument used in this study was the Service, Forehand and backhand test. The subjects in this study were 10 athletes in the Tennis club Medan. The results of this study indicate that the basic technic skills are categorized as "average", as many as 1 athlete (10%) who has service skills in the category of poor, 1 athlete (10%) categorized bellow average, 5 athletes (50%) in average, 2 athletes (20%) in above average and 1 athlete (10%) in excellent category. Basic Forehand technique skill in the category of "good", 1 athlete (10%) who has technique skills with very low category, 2 athletes (20%) in less category, 3 athletes (30%) in average category, 4 athletes (40%) are in good category. Basic Backhand technical skill in with the category of "less", 4 athletes (40%) having the technique with less category, 3 athletes (30%) in average category, 2 athletes (20%) in good category and 1 athlete (10%) is very well categorized. 8 (80%) athletes heve below average in basic technic and 2 (20%) athletes heve average.